Evolution of the physical characteristics of the French womens rugby seven and union: A ten-year longitudinal analysis - Imbert, S.; Delforge, E.; Boissière, J.; Joncheray, H.; Vincent, J.; Daussin, F. N. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Rugby union and rugby sevens are demanding and intermittent team sports with collisions, high intensity runs interspaced with periods of low intensity activity. While the physical characteristics development of elite male rugby union and rugby seven players have been widely described, much less is known about female international players. This present study aims to assess physical changes over time of women`s rugby union players (backs and forwards) and women`s seven players.